First Record of Anisoptera (Insecta: Odonata) from mid-Cretaceous Burmese Amber - Schädel, Mario; Bechly, Günter (Zootaxa, 2016)
The fossil dragonfly Burmalindenia imperfecta gen. et sp. nov. is described from mid-Cretaceous Burmese amber as the first record of the odonate suborder Anisoptera for this locality and one of the few records from amber in general. The inclusion comprises two fragments of the two hind wings of a dragonfly. The fossil can be attributed to a new genus and species of the family Gomphidae, presumably in the subfamily Lindeniinae, and features a strange teratological phenomenon in its wing venation.